Push – pull – mooring determinants of non-Muslims’ withdrawal from Islamic banking: evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Lelchumanan, Bawani; Ah Mand, Abdollah; Khaliq, Ahmad (Emerald Publishing, 2024)
Purpose – This study aims to attempt to investigate the factors that influence non-Muslims’ withdrawal behavioural intention from Islamic banking in Malaysia. Design/methodology/approach – The push–pull–mooring approach is used to examine the determinants of withdrawal intention by non-Muslims from Islamic banking in Malaysia. Variables used in this study include religiosity (RELG) under push, deposit guarantee (DG), rate of return (RR), Islamic banks’ specific factors (IBSF) under pull and mooring factors as social influence (SI) and voluntary switching (VS) as the determinants of withdrawal intention from Islamic banking. In this study, the SPSS Statistics Version 22 and smart partial least squares were used to measure the withdrawal level. Findings – Three variables, namely, SI, RR and IBSF are found to significantly influence the withdrawal behaviour intention. Meanwhile, three other variables, namely, RELG, DG and VS are not significant. Practical implications – This study provides valuable insights pertaining to non-Muslim consumer withdrawal behaviour from Islamic banks. Bank managers, marketers and regulators could use these findings in developing effective strategies to increase and retain customer withdrawal. Originality/value – This study expands the understanding of key determinants of the non-Muslim withdrawal behaviour from Islamic banks in Malaysia. To the best of the authors’ knowledge, this research is among the pioneer empirical study to assess the issue